Local Food Diversification as a Pillar of Sustainable Food Development: A Critical Review of Global and Local Perspectives - Fiza, Nora; Erwin; Nazir, Novizar; Tanjung, Faidil (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study presents a critical narrative review of national and international literature published between 1995 and 2024 to examine the conceptual and empirical contributions of local food diversification in building sustainable food systems. Local food diversification plays a strategic role in building a more equitable, inclusive, and sustainable food system. A narrative critical review method was employed, allowing for thematic synthesis of peer-reviewed publications obtained from databases such as Scopus, ScienceDirect, Google Scholar, and accredited national journals. Literature selection focused on the keywords: local food diversification, food security, agroecology, local wisdom, and sustainable food systems. The collected data were analysed by mapping findings into five key dimensions: ecology, socio-culture, economy, technology, and policy and institutions. Findings highlight that agroecological diversification based on local biodiversity improves climate resilience and food availability, while also preserving cultural identity and empowering rural economies. Technological innovation and participatory policy approaches are essential to support local food systems. Strengthening multi-sector collaboration, research funding, and community participation is key to positioning local food diversification as a foundation for inclusive and resilient national food policy. This study emphasises the importance of strengthening institutions, research funding, and cross-sector collaboration to make local food diversification the foundation of the national food security strategy. By placing local values and diversity as pillars of policy, Indonesia can realise a future food system that is resilient, sovereign, and aligned with the principles of sustainability. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 15: Life on Land